Reviews - Rowley-Conwy, Peter; Nielsen, Svend (Journal of Danish Archaeology, 1983)
Reviews: THORLEIF SjØVOLD ( ed.): Jntroduksjonen av jordbruk i Norden. Oslo Marek Zvelebil: From Forager to Farmer in the Boreal Zone. BAR International Ser. 115. Oxford 1981 (by Peter Rowley-Conwy) Ester Boserup: Population and Technological Change. Chicago 1981 (by Svend Nielsen)